IMPROVING THE PROFESSIONAL COMPETENCE OF THE FUTURE CHOREOGRAPHY TEAM LEADER (American Journal of Pedagogical and Educational Research, 2023)
This article talks about improving the professional competence of the future choreography team leader. In the article, based on information from the cultural field, specific aspects of improving the professional competence of the future choreography team leader were studied and analyzed on the basis of available scientific literature.